Restorative therapy using microglial depletion and repopulation for central nervous system injuries and diseases - Shi, Weipeng; Zhang, Jing; Shang, Zhen; Zhang, Yingze; Xia, Yanzhi; Fu, Haitao; Yu, Tengbo (Frontiers in Immunology, 2022)
Microglia are important resident immune cells in the central nervous system (CNS) and play an important role in its development, homeostasis, and disease treatments. Activated microglia perform diverse functions in mouse models of CNS neurodegenerative diseases or deficits. In humans, microglia have been linked to various neurodegenerative diseases. Following brain or spinal cord injury, microglia express pro- and anti-inflammatory phenotypes at different stages of recovery. With the development of pharmacological and genetic tools for microglial depletion, studies have demonstrated that microglial depletion exerts both positive and negative effects in the treatment of CNS diseases. Notably, microglial depletion provides an empty niche that stimulates production of new microglia. Microglial depletion and repopulation can not only treat diseases by eliminating dysfunctional microglia but can also provide an indication of the molecular mechanisms of diseases. Although this approach has shown impressive results, its use is still in its infancy. In this review, we summarize the current pharmacological and genetic tools for microglial depletion and highlight recent advances in microglial repopulation therapy for the treatment and functional recovery of neurological diseases and deficits. Finally, we briefly discuss the therapeutic challenges and prospective uses of microglial repopulation therapy.